2019
DOI: 10.1093/neuonc/noz014
|View full text |Cite
|
Sign up to set email alerts
|

Updates in the management of intradural spinal cord tumors: a radiation oncology focus

Abstract: Primary spinal cord tumors represent a hetereogeneous group of central nervous system malignancies whose management is complex given the relatively uncommon nature of the disease and variety of tumor subtypes, functional neurologic deficits from the tumor, and potential morbidities associated with definitive treatment. Advances in neuroimaging; integration of diagnostic, prognostic, and predictive molecular testing into tumor classification; and developments in neurosurgical techniques have refined the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 104 publications
(114 reference statements)
1
17
0
Order By: Relevance
“…Our study aimed to investigate the impact of steroids and NLR in NSCLCBM patients. In concordance with the literature, our study showed that the use of upfront steroids was associated with reduced OS and PFS in NSCLCBM treated with ICI 11 14 . Arbour et al 13 reported that upfront use of steroids (> 10 mg of prednisone) was associated with decreased OS in patients with NSCLC.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study aimed to investigate the impact of steroids and NLR in NSCLCBM patients. In concordance with the literature, our study showed that the use of upfront steroids was associated with reduced OS and PFS in NSCLCBM treated with ICI 11 14 . Arbour et al 13 reported that upfront use of steroids (> 10 mg of prednisone) was associated with decreased OS in patients with NSCLC.…”
Section: Discussionsupporting
confidence: 91%
“…The interaction between radiation therapy and ICI has been previously documented 11 . In our cohort, 126 patients of 171 received only SRS, eight patient received only WBRT, 34 patients received WBRT and SRS and zero patients only underwent a craniotomy after the diagnosis of BM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the scarcity of intramedullary metastases, high-level evidence and guidelines on their management are lacking. Current treatment options include microsurgical resection, chemotherapy, fractionated radiotherapy and stereotactic radiosurgery (SRS) as well as a combination of them [ 2 , 15 , 16 , 17 ]. In recent years, several studies have been published on the efficacy of surgery and radiotherapy for local control and their effect on neurological deficits [ 5 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%